2018
DOI: 10.1016/j.celrep.2018.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Kruppel-like Factor 9 in Excitatory Neurons Protects against Chronic Stress-Induced Impairments in Dendritic Spines and Fear Responses

Abstract: Stress exposure is associated with the pathogenesis of psychiatric disorders, including post-traumatic stress disorder (PTSD) and major depressive disorder (MDD). Here, we show in rodents that chronic stress exposure rapidly and transiently elevates hippocampal expression of Kruppel-like factor 9 (Klf9). Inducible genetic silencing of Klf9 expression in excitatory forebrain neurons in adulthood prior to, but not after, onset of stressor prevented chronic restraint stress (CRS)-induced potentiation of contextua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…This is consistent with a recent report that injection of cortisol into eggs leads to increased neurogenesis in the larval brain 10 . In this regard it is interesting that klf9 is a stress-responsive gene that regulates neural differentiation and plasticity 35,46 . The long-term dysregulation of the HPA/I axis caused by early life exposure to chronic stress and/or chronically elevated cortisol suggests that the exposure perturbs brain development and activity.…”
Section: Scientific Reports |mentioning
confidence: 99%
“…This is consistent with a recent report that injection of cortisol into eggs leads to increased neurogenesis in the larval brain 10 . In this regard it is interesting that klf9 is a stress-responsive gene that regulates neural differentiation and plasticity 35,46 . The long-term dysregulation of the HPA/I axis caused by early life exposure to chronic stress and/or chronically elevated cortisol suggests that the exposure perturbs brain development and activity.…”
Section: Scientific Reports |mentioning
confidence: 99%
“…PSD-95 is believed to be a key regulator of dendritic morphology and when overexpressed it adversely affects dendritic morphology and complexity (Charych et al 2006). We extended these findings and proved that continuous lithium treatment followed by a period without lithium acts positively on dendritic maturation and complexity, which is arguably a morphometric parameter that has important functional implications in memory function and anti-stress mechanisms (Besnard et al 2018). We hypothesized that this is attributable to key regulatory proteins involved in cytoskeletal rearrangements (Tppp) and synaptic transmission (GAD65).…”
Section: Identification Of Mechanismsmentioning
confidence: 74%
“…This is consistent with a recent report that injection of cortisol into eggs leads to increased neurogenesis in the larval brain 24 . In this regard it is interesting that klf9 is a stress-responsive gene that regulates neural differentiation and plasticity 8,19 . The long-term dysregulation of the HPA/I axis caused by early life exposure to chronic stress and/or chronically elevated cortisol suggests that the exposure perturbs brain development and activity.…”
Section: Discussionmentioning
confidence: 99%
“…In epidermis many of the genes repressed by Klf9 are also activated by the GR 6 . It was recently shown that klf9 is upregulated in mouse hippocampus in response to the onset of chronic stress, and blocking that upregulation prevents chronic stress-induced pathologies 19 . In the same study it was also shown that hippocampuses of women with major depression were found to overexpress KLF9 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation